Population based cancer registry in Nepal. (2018)
SUMMARY: Background Nepal Health Research Council (NHRC), a national apical body of Government of Nepal, responsible for promoting scientific study and quality health research in the country, has started Population Based Cancer Registry (PBCR) in Nepal since January 1, 2018. Starting with Kathmandu Valley, PBCR has been expanded to other districts as well in order to have representative information throughout the country. Kathmandu valley cancer registry covers the population of Kathmandu, Bhaktapur and Lalitpur districts of Province 3, cancer registries in Siraha, Saptari, Dhanusha and Mahottari covers the population of four districts of province 2, and eastern and western Rukum districts cancer registry covers the population of Rukum district of Province 5 and 6. NHRC is making close collaboration with Ministry of Health and Population (MoHP) and WHO to establish the registry in Nepal, which has been technically supported by International Agency for Research on Cancer (IARC). The objective of the registry is to generate evidence on cancer incidence, patterns and trends of disease and mortality related to cancer in the defined population, and also to enhance national capacity for sustainable PBCR in Nepal. The cancer registry data will be useful in planning cancer control activities and to strengthen cancer care services by the government of Nepal. The registry office is located in NHRC, Ramshah Path, Kathmandu. Population Covered According to the census 2011, the total population of Nepal is 2,64,94,504. Population Based Cancer Registry in Nepal which includes registry in province no. 2, 3 and 6 covers 20.3% (53,84,523)of the total population as shown in the table below. Cancer Registry Province Metropolitan City / Municipalities Rural Municipalities Population PBCR Kathmandu valley 3 21 3 2,517,023 PBCR Siraha, Saptari, Dhanusha and Mahottari 2 39 28 2,658,933 PBCR Rukum 5 and 6 3 6 2,08,567 Total 63 37 53,84,523 Methodology The methodology of data collection by the registry is both active and passive surveillance depending upon the data sources. There are two major ways through which data are obtained for the registry. One is from the facilities which include hospital, pathology laboratory, hospice, department of health service bipanna section and civil registration. The registry personnel visit these sources at regular intervals and actively collect cancer cases data available there. The data is collected from the records of the sources since January 2018 and recorded in the standard format. Other is from the community in which orientation is given to the Health Coordinators at each Municipality/Rural Municipality, Health In-charges and even the Female Community Health Volunteers (FCHVs) wherever necessary. Data is then obtained by FCHVs from the population through home visit submitted to the Health In-charges. The Health In-charges submit data to the Health Coordinators and the Health Coordinators to the NHRC office on monthly basis. The obtained data from all these sources is verified for the completeness, accuracy and residence andthen entered into CanReg5 Software at the NHRC office. For the Kathmandu Valley cancer registry, there are many cancer diagnostic and treatment facilities in Kathmandu valley. Thus, most of the cases can be obtained from these facilities within Kathmandu, Bhaktapur and Lalitpur districts. However, people sometimes visit B.P. Koirala Memorial Cancer Hospital (BPKMCH), Bharatpur, Chitwan around 200 km away from the valley. So we collect the data of the cases of our selected districts from there as well. Since people also visit India for cancer treatment, we have coordinated to some renowned cancer hospitals in India to collect data of cancer patients. Nevertheless, for other two registries of Province no. 2 and 6, there are not any diagnostic and treatment facilities within Siraha, Saptari, Dhanusha, Mohattari, and Rukum districts. Thus, besides the data from the communities through Female Community Health Volunteers, health post incharge and health coordinators of these districts, PBCR has coordinated with different diagnostic and treatment facilities inside and outside Kathmandu valley such as Banke, Bardiya, Nepalgunj, Dharan, Birgunj, Biratnagar, Chitwan and even with India. Result The data collection of cancer cases from all the sources has been completed till August, 2018. Out of total 5260 cases (new and old) checked by PBCR from various sources, 2612 cases have been found to be new cases. The incidence (new case) was separated according to the date of diagnosis, and all the cases were contacted through the phone calls in order to confirm their residence. The verification and residence confirmation of the cases are completed till May 31st 2018, which shows a total of 702 cancer cases from Kathmandu Valley,256 cancer new cases from Siraha, Saptari, Dhanusha and Mahottari and 23 new cases from East and West Rukum. The Annual Report of PBCR 2018 is expected to be completed and published by September 2019. However, interim analysis of Kathmandu Valley registry until May 2018 has been completed. The major findings are summarized below In 702 cases from Kathmandu Valley, cancer incidence is higher among females comparing to the males (379 Vs 323). The higher incidence is found among the age group of 70-74 years followed by the age group of 65-69 years and then 60-64 years with an age specific rate of 230.5, 203 and 185.3 per 100,000 respectively. In male the top leading cancer site is lungs followed by lip and oral cavity, colon and rectum, stomach, pharynx, bladder, larynx, pancreas, gall bladder and kidney. In females, breast, lungs, cervix uteri, thyroid, gall bladder, colon and rectum, ovary, stomach, lip and oral cavity, Non-Hodgkin's disease and brain are the leading cancer sites. There might be under registration or under diagnosis of cancer cases as the pediatric cases are found very less. Similarly, we may have missed clinically diagnosed and radiological diagnosed cases. The cases which primary site is unknown are only 6.2% in males and 4% in females which signifies the quality of diagnostic information as well as proper documentation of health care providers.